1997
DOI: 10.1002/marc.1997.030180701
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation of poly(ε‐caprolactone) with cyclodextrin

Abstract: Poly(c-caprolactone) was found to form inclusion complexes with a-cyclodextrin to give crystalline compounds. The complexes are stoichiometric one-to-one (cyclodextrin : monomer unit) compounds. The yields of the complexes decreased with increasing the molecular weight of the polymer. They were characterized by IR, 'H NMR, 13C CP/MAS NMR, and X-ray diffraction. The inclusion modes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 14 publications
8
94
0
Order By: Relevance
“…For this purpose, lin-pPR 2 with a 1:1 ε-CL:α-CD ratio was prepared from a linear PCL of 2 kg mol −1 and subsequently analyzed by SANS. As previously observed by Harada et al, [ 6,21 ] it is worth noting that thanks to the use of short PCL chains, lin-pPR 2 as well as star-pPR (for which star-PCL arms have an M n of 2.5 kg mol −1 ) achieve a much larger α-CD coverage ratio than lin-pPR 10 . In the case of lin-pPR 2 , even at the lowest tested temperature (i.e., T = 35 °C), it is observed that the scattered intensity profi le corresponds exactly to the sum of the profi les of linear PCL chains and free CDs proving that CD dethreading occurred immediately after solubilization in DMSO ( Figure S19, Supporting Information).…”
Section: Structure Of Star-pprs In Dmsomentioning
confidence: 68%
See 2 more Smart Citations
“…For this purpose, lin-pPR 2 with a 1:1 ε-CL:α-CD ratio was prepared from a linear PCL of 2 kg mol −1 and subsequently analyzed by SANS. As previously observed by Harada et al, [ 6,21 ] it is worth noting that thanks to the use of short PCL chains, lin-pPR 2 as well as star-pPR (for which star-PCL arms have an M n of 2.5 kg mol −1 ) achieve a much larger α-CD coverage ratio than lin-pPR 10 . In the case of lin-pPR 2 , even at the lowest tested temperature (i.e., T = 35 °C), it is observed that the scattered intensity profi le corresponds exactly to the sum of the profi les of linear PCL chains and free CDs proving that CD dethreading occurred immediately after solubilization in DMSO ( Figure S19, Supporting Information).…”
Section: Structure Of Star-pprs In Dmsomentioning
confidence: 68%
“…Then, using small angle neutron scattering (SANS) experiments, the star-pPR structure in DMSO-d 6 was investigated showing that isolated nanoplatelets of star-pPRs could be obtained. As an application, PCL:star-pPR core:shell fi bers were prepared by coaxial electrospinning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystalline structures of the inclusion complexes of a-CDs with lowmolecular-weight compounds can be classified as ''cage type'' or ''channel type''. [38][39][40] The diffraction peaks at 19.87 and 22.618 are characteristics of the crystals of a-CD/ PEO ICs adopting a channel-type structure. [35,40] It is noted that the effect of the terminal POSS groups on the crystal structures of the organic/inorganic polyrotaxanes is quite dependent on the molecular weight of PEO used for the synthesis of the polyrotaxanes.…”
Section: Crystal Structures Of Organic/inorganic Polyrotaxanesmentioning
confidence: 99%
“…[8,9] It is known that partially and fully methylated CDs can also form ICs and the stability of the ICs formed depends on the size and shape of the guest molecule. [10] While there have been so many publications about the inclusion phenomena of the natural CDs with polymers, such as poly(e-caprolactone), poly(ethylene adipate), poly(trimethylene adipate), and poly(1,4-butylene adipate), [11][12][13][14][15] only a few investigations on the complex formation of modified CD with polymers have been reported. [9,[16][17][18][19][20][21] Okada et al [9] found that methylated CDs selectively form ICs with hydrophobic polymers and that the hydrophobic interaction between methylated CDs and polymers is one of the most important factors for complexation, as found also for unmodified CDs.…”
Section: Introductionmentioning
confidence: 99%